Caring Through Web-Based Communication: A Qualitative Evaluation of a Nursing Intervention to Create Holistic Well-Being Among Patients With Hematological Disease. (September 2018) - Högberg, Karin M.; Sandman, Lars; Nyström, Maria; Stockelberg, Dick; Broström, Anders
Purpose: To examine how written communication between patients with hematological diseases and a nurse within a web-based communication service can be caring.Design: The study is based on qualitative deductive content analysis of 109 written messages between 10 patients and a responding nurse. The evaluated nursing intervention is a web-based communication service where patients could request support from a responding nurse during 2 months of use. A structured theoretical matrix based on Swanson's theory of caring including compassion, competence, and upholding trust is used for the analysis.Findings: Nursing compassion emerges when patients share personal matters and the nurse has an opportunity to explicitly display genuine interest and understanding. Nursing competence is required when patients ask for or are in need of information, advice, and emotional support. The nurse can uphold trust when compassion and competence are exhibited and patients share their innermost feelings.Conclusions: Web-based communication has the potential to contribute to holistic well-being according to Swanson's theory of caring. The written word lasts, can be read repeatedly, and in connection with writing there is time for reflection. However, the lack of nonverbal cues makes it important that the nurse answers in a fully accurate and explicitly caring way.